The effects of cooperative learning on students' achievement in reading comprehension - Lekha V. M. Asok Kumar, 1986-; Norzarina Sulong, supervisor; Fakulti Pendidikan (2011)
Project Paper (Sarjana Muda Sains serta Pendidikan (Pengajaran Bahasa Inggeris sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2011